Analysis of Mammography BI-RADS Distribution and Follow-up Ultrasound Assessment: A Single-Center Study - Kankaya B; Buyukasik S; Altundal YE; Topcu FS; Rahmanbakhsh P; Etemad A; Kapan S; Alis H (Breast Cancer: Targets and Therapy)
Burak Kankaya,1 Suleyman Buyukasik,1 Yusuf Emre Altundal,1 Feyza Sonmez Topcu,2 Paria Rahmanbakhsh,1 Ayden Etemad,1 Selin Kapan,1 Halil Alis1 1Department of General Surgery, Faculty of Medicine, Istanbul Aydin University, Istanbul, Turkey; 2Department of Radiology, Faculty of Medicine, Istanbul Aydin University, Istanbul, TurkeyCorrespondence: Yusuf Emre Altundal, Department of General Surgery, Istanbul Aydin University Faculty of Medicine, Besyol Mah, Akasya Sok. No: 4, Kucukcekmece, Istanbul, 34295, Turkiye, Email yusufemrealtundal@aydin.edu.trPurpose: Our study has three main aims: 1) to assess the distribution of Breast Imaging Reporting and Data System (BI-RADS) classifications in a cohort of Turkish women undergoing screening mammography, 2) to analyze the frequency and non-completion rates of recommended follow-up ultrasound (US) examinations, and 3) to examine the outcomes of completed follow-up US examinations. Our goal was to evaluate potential gaps in the current breast cancer screening process by analyzing BI-RADS classifications, follow-up completion rates, and outcomes of completed ultrasound examinations.Patients and Methods: This retrospective study analyzed 1761 Turkish women who underwent screening mammography from 2020– 2022 at the Istanbul Aydin University General Surgery Clinic, Istanbul, Turkey. We assessed the distribution of BI-RADS classifications, analyzed the frequency and non-completion rates of recommended follow-up US, and examined the outcomes of completed follow-up US examinations. Chi-square tests of independence and Spearman’s rank correlation test were used to analyze the data.Results: Our study revealed three key findings: 1) Over half of mammograms (55.9%) were classified as BI-RADS 0, requiring further imaging. 2) Nearly one-third of patients who recommended US examinations (31.91%) did not complete recommended follow-up ultrasound appointments. 3) Among those who completed follow-up ultrasonography, almost one-third (29.7%) were reclassified as BI-RADS 3 or higher. Notably, 2.3% (n=18) were classified as BI-RADS 4 or 5, suggesting findings suspicious for malignancy.Conclusion: Our findings highlight the crucial role of follow-up US in breast cancer screening. The high rate of initial BI-RADS 0 classifications using mammography, coupled with the significant non-completion rate for follow-up US examinations, particularly among older age groups, highlights potential gaps in the current screening process.Keywords: breast ultrasonography, mammography, breast cancer, early diagnosis, BI-RADS classification